Transient expression from cab-m1 and rbcS-m3 promoter sequences is different in mesophyll and bundle sheath cells in maize leaves. - Bansal, K C (1992)
Cell-specific and light-regulated expression of the beta-glucuronidase (GUS) reporter gene from maize cab-m1 and rbcS-m3 promoter sequences was studied in maize leaf segments by using an in situ transient expression microprojectile bombardment assay. The cab-m1 gene is known to be strongly photoregulated and to be expressed almost exclusively in mesophyll cells (MC) but not in bundle sheath cells (BSC). Expression of GUS from a 1026-base-pair 5' promoter fragment of cab-m1 is very low in dark-grown leaves; GUS expression is increased about 10-fold upon illumination of dark-grown leaves. In illuminated leaves, the ratio of GUS expression in MC vs. BSC is about 10:1. The cab-m1 region between 868 and 1026 base pairs 5' to the translation start confers strong MC-preferred expression on the remainder of the chimeric gene in illuminated leaves, but a region between -39 and -359 from the translation start is required for photoregulated expression. Transcripts of rbcS-m3 are found in BSC but not in MC and are about double in BSC of greening dark-grown seedlings. In contrast to the behavior of the cab-m1-GUS construct, GUS expression driven by 2.1 kilobase pairs of the rbcS-m3 5' region was about twice as high in MC as in BSC of unilluminated dark-grown maize leaves. The number of BSC, but not MC, expressing GUS nearly doubled upon greening of bombarded etiolated leaves. These data suggest that the 5' region of rbcS-m3 used here could be responsible for most of the light-dependent increase in rbcS-m3 transcripts observed in BSC of greening leaves and that transcriptional or posttranscriptional mechanisms are responsible for the lack of rbcS-m3 transcripts in MC.